Exploring Teachers' Perceptions of AI-Powered Classroom-Based Assessment Tools in ESP Class - Difa Salsa Maulidyah (Indonesian Journal of Foreign Language Studies, 2025)
The growth of technology in this globalization era has led to the innovation of a digital learning platform called artificial intelligence (AI). Artificial intelligence (AI) was a good innovation for teachers and students, helping them during the teaching and learning activities. Moreover, Artificial intelligence (AI) helped the teachers create interactive material for ESP students, which made it more difficult to find specific materials for ESP classes. This study was conducted by interviewing ESP lecturers who teach ESP classes to university students. This study used the semi-structured interview to explore the teachers’ perception of using AI in ESP Course Quizziz, eleven labs, ChatGpt, Google Translate, DeepL translator, Hot Potatoes, TTS maker, Kahoot, Padlet, opexams, and others as an AI classroom-based assessment tools during the teaching and learning process. This study found that some Artificial Intelligences (AI) were beneficial for the ESP lecturer, which made it easier to make ESP materials, teach the ESP students, and assessed students to check their understanding of the subject. The students were very motivated and more interactive during the learning process.